Practical child and adolescent psychopharmacology - Kutcher, Stanley P. (Cambridge child and adolescent psychiatry series., 2002)
This important book synthesises the most recent findings about drug treatment for children with a broad range of psychiatric disorders, discussing tolerability, efficacy and appropriate use within a social and developmental context. It is essential reading for all mental health professionals to inform practice and improve patient outcomes.